A fast calculation tool for accessing the shading effect of surrounding buildings on window transmitted solar radiation energy. (June 2022) - Wen, Jianxiu; Yang, Shiji; Xie, Yongxin; Yu, Juan; Lin, Borong
Highlights: A parametric study with 2500 models using EnergyPlus was carried out. A rapid method to assess the shading effect of surrounding buildings was developed. The method can greatly shorten calculation time while keeping an acceptable accuracy. Suggestions were provided for designers achieving energy-efficient design. Abstract: Most existing Urban Building Energy Modeling (UBEM) tools cannot simultaneously achieve fast and accurate simulation of regional building energy consumption with the consideration of shading effect from surrounding buildings. This study explored how the different designs of surrounding buildings affect the window transmitted solar radiation energy (WTSRE) of the target building by performing a parametric study using EnergyPlus, and proposed one method that can rapidly assess the shading effect of surrounding buildings at the design stage based on the databases obtained from the parametric study. A SketchUp plug-in named MOOSAS-FastSolar was developed based on the proposed method. By comparing the calculation results of the MOOSAS-FastSolar with the simulation results of EnergyPlus, the method developed by this research can greatly shorten the calculation time from more than 1 h to tens of seconds while keeping the accuracy of the calculation results within an acceptable range (the computational error is less than 15%). In addition, from the parametric simulation results, some recommendations were provided to help building designers achieve energy-efficient design at the conceptional design stage.